ô€°¸ô©¥ô›ô‚©¦ô€¡Ÿô€ ¾ô€¡…ô€¡¿ô€¼ ô€´¾ô¼²ô€¡¢ôƒ ô‚ (COLLABORATIVE WRITING IN TEACHING SAKUBUN) (Language Circle: Journal of Language and Literature, 2011)
This study was intended to find out how collaborative writing gives better effects to thestudent’s Japanese ability in writing. There were three aspects that investigated: (1) Teachinglearning process, (2) Learner and teacher finding problems in collaborative writing, (3)Student’s suggestion of collaborative writing. This study employed descriptive qualitativedesign by using classroom observations and interview method to collect the data. The majorfindings of this study are: (1) Collaborative writing enable student to practice and developwriting skills, however, the lack of grammar ability cause peer correction not appropriate, (2)Teaching learning sakubun becomes more various by using this technique.